Bladder pain syndrome in men. Issue 6 (15th November 2022) - Derbyshire, Laura; Pearce, Ian
Abstract : Bladder pain syndrome is a subset of chronic pelvic pain syndrome and a diagnosis of exclusion. It can significantly reduce quality of life and requires clinicians to have a high index of suspicion and provide prompt evidence‐based multidisciplinary management to patients to prevent ongoing distress.